DECISION SUPPORT SYSTEM FOR PROVIDING WORK ALLOWANCES AND PUNISHMENTS TO EMPLOYEES USING THE AHP AND SMART METHOD - Berti Sari Br Sembiring; Mahdianta Pandia; Fransisca Br Sebayang; Harianta Sembiring (INFOKUM, 2022)
From the results of the study it can be concluded, among others: The decision support system that was built was very helpful to speed up data processing in decision making for the provision of work benefits and punishments to employees. The SMART method is a suitable method to be applied in decision making by sharing alternatives, especially determining the provision of work benefits and punishments to employees quickly and precisely. The level of accuracy of the test results using the SMART method is 100%. The decision support system application that is built is dynamic in terms of determining criteria and weighting. So, it can be changed according to the needs of the company in providing work benefits and punishments